2021
DOI: 10.1055/a-1480-0428
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a new flexible 19 G EUS needle in pancreatic solid lesions located in the head and uncinate process: A prospective multicenter study

Abstract: Background and study aims The poor flexibility of large-bore EUS needles often leads to technical failure when sampling from the duodenum. The aim of this study was to evaluate the technical and diagnostic performances of a new Menghini tip 19G nitinol EUS needle for sampling pancreatic solid lesions in the head and uncinate process. Patients and methods This was a European prospective multicenter single-arm study. A maximum of four passes were allowed. In case of failure, different needles were perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 . This information is in accordance with previous publications with the esophageal ultrasound (EUS) where the gastroenterologists used larger 19G needles 21 , 22 . However; based on the published literature regarding cryo biopsies for endobronchial lesions it was observed that larger samples were obtained 23 .…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 . This information is in accordance with previous publications with the esophageal ultrasound (EUS) where the gastroenterologists used larger 19G needles 21 , 22 . However; based on the published literature regarding cryo biopsies for endobronchial lesions it was observed that larger samples were obtained 23 .…”
Section: Discussionsupporting
confidence: 91%
“…In the single case of technical failure, concerning an uncinate process cyst, the endoscope/needle set position did not allow the forceps passage. The use of new nitinol-based needles with enhanced flexibility may be a solution to overcome this difficulty, but this should be a subject for future studies [19, 20]. The results from our series are similar to the experience of other groups [7, 9, 21, 22], with several recent meta-analyses confirming the favorable diagnostic accuracy of TTNB and its superiority over FNA cytology [12, 13, 18].…”
Section: Discussionsupporting
confidence: 80%
“…From 3445 studies identified using the search strategy, we included 8 studies,[ 10 11 12 20 21 22 23 24 ] [ Figure 1 ] recruiting 2147 patients. Out of these 8 studies, 5 were retrospective series,[ 11 12 20 22 24 ] 2 RCTs,[ 10 23 ] and 1 study was a prospective series.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 8 studies, 5 were retrospective series,[ 11 12 20 22 24 ] 2 RCTs,[ 10 23 ] and 1 study was a prospective series. [ 21 ] Specifically, 1 large multicenter RCT[ 10 ] and 4 retrospective series[ 12 20 22 24 ] were studies focused on the direct comparison between EUS-FNB + ROSE versus EUS FNB alone, whereas another retrospective study[ 11 ] was a 4-arm retrospective series comparing EUS FNA alone versus EUS-FNA + ROSE versus EUS-FNB alone versus EUS-FNB + ROSE, the prospective series by Gines et al [ 21 ] and the RCT by Nagula et al [ 23 ] reported a subgroup analysis based on the use of ROSE. All the studies were published as full-text manuscripts except the retrospective study by Mahmood et al [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation